Free living marine nematodes of the genus Parodontophora (Axonolaimidae) from the East China Sea, with descriptions of five new species and a pictorial key - Li, Yongxiang; Guo, Yuqing (Zootaxa, 2016)
Five new species of free living marine nematodes belonging to genus Parodontophora are described from intertidal areas of Fujian Province, East China Sea. P. aequiramus sp. nov. is identified by the amphid with the same length of dorsal branch and ventral branch, opisthocephalic setae arranged as (2D-1V)2, precloacal supplements and armilliths present; Parodontophora irregularis sp. nov. is characterized by arranged irregularly opisthocephalic setae, excretory pore near cephalic setae at the anterior part of buccal cavity and precloacal supplements present; Parodontophora huoshanensis sp. nov. can be distinguished by the amphid 0.77–0.83 times the length of the buccal cavity, opisthocephalic setae arranged as (2D-1V)2 and precloacal supplements present; Parodontophora microseta sp. nov. is characterized by the amphid 1.71–2.1 times the length of the buccal cavity, opisthocephalic setae arranged as (1D-1V)2, precloacal supplements present and anterior gonad to the right and posterior gonad to the left of the intestine; Parodontophora paramicroseta sp. nov. is characterized by the amphid 1.35–1.5 times the length of the buccal cavity, opisthocephalic setae arranged as (1D-1V)2, precloacal supplements present and anterior gonad to the left and posterior gonad to the right of the intestine. A pictorial key to the valid species of Parodontophora Timm, 1963 is given.